2015
DOI: 10.4254/wjh.v7.i25.2610
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological differences utilizing the nonalcoholic fatty liver disease activity score criteria in diabetic (type 2 diabetes mellitus) and non-diabetic patients with nonalcoholic fatty liver disease

Abstract: AIM:To study clinical and histopathological features of nonalcoholic fatty liver disease (NAFLD) in patients with and without type 2 diabetes mellitus (T2DM) using updated nonalcoholic steatohepatitis clinical research network (NASH-CRN) grading system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…Besides phenotypically readily apparent subtypes of NASH patients, such as lean vs. obese patients (Kumar and Mohan, 2017 ) or diabetic vs. non-diabetic patients (Puchakayala et al, 2015 ), recent efforts on subtyping NAFLD/NASH patients on the basis of their serum metabolome (Alonso et al, 2017 ; Iruarrizaga-Lejarreta et al, 2017 ) have revealed that patients may also be classified on the basis of their molecular disease patterns and have provided insight into molecular pathways that may be impaired in some but not other patients (i.e., synthesis of S-adenosylmethionine). A similar analysis in the Ldlr −/− .Leiden mouse revealed that on the metabolome level this model reflects a substantial proportion of NAFLD/NASH patients (Morrison et al, 2017 ) but the underlying disease mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides phenotypically readily apparent subtypes of NASH patients, such as lean vs. obese patients (Kumar and Mohan, 2017 ) or diabetic vs. non-diabetic patients (Puchakayala et al, 2015 ), recent efforts on subtyping NAFLD/NASH patients on the basis of their serum metabolome (Alonso et al, 2017 ; Iruarrizaga-Lejarreta et al, 2017 ) have revealed that patients may also be classified on the basis of their molecular disease patterns and have provided insight into molecular pathways that may be impaired in some but not other patients (i.e., synthesis of S-adenosylmethionine). A similar analysis in the Ldlr −/− .Leiden mouse revealed that on the metabolome level this model reflects a substantial proportion of NAFLD/NASH patients (Morrison et al, 2017 ) but the underlying disease mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The association between T2DM and the more severe forms of NAFLD was also reported by Loomba et al [84] in an observational study enrolling 1,069 T2DM patients with biopsy-proven NAFLD, documenting a significant association between history of diabetes mellitus, NASH and advanced fibrosis, even after adjusting for age, sex, body mass index, ethnicity, and presence of metabolic syndrome. Moreover, in a retrospective analysis of 235 patients with biopsy-proven NAFLD with and without T2DM, Puchakayala et al [85] documented that among T2DM patients with NAFLD, the prevalence of advanced fibrosis and ballooning were significantly greater as compared to patients with NAFLD but without T2DM. Interestingly and importantly, in the multivariate regression analysis, T2DM was associated with NASH and fibrosis in all patients with NAFLD [85] .…”
Section: Prevalence Of Nafld In Patients With Diabetes Mellitusmentioning
confidence: 99%
“…Moreover, in a retrospective analysis of 235 patients with biopsy-proven NAFLD with and without T2DM, Puchakayala et al [85] documented that among T2DM patients with NAFLD, the prevalence of advanced fibrosis and ballooning were significantly greater as compared to patients with NAFLD but without T2DM. Interestingly and importantly, in the multivariate regression analysis, T2DM was associated with NASH and fibrosis in all patients with NAFLD [85] . These data were additionally replicated in a recent meta-analysis by Younossi et al [86] including 80 observational studies for a total of nearly 49,500 individuals with T2DM (mean age: 58 years; mean body mass index: 28 kg/m 2 ; percentage of men: 53%).…”
Section: Prevalence Of Nafld In Patients With Diabetes Mellitusmentioning
confidence: 99%
“…NASH can lead to fibrosis and eventually cirrhosis (Ratziu et al, 2010). Patients with type 2 diabetes and NAFLD tend to have more advanced stages of NAFLD with higher rate of ballooning and advanced fibrosis than patients with NAFLD without type 2 diabetes (Puchakayala et al, 2015). Based on imaging studies, the global prevalence of NAFLD is about 25%.…”
Section: Introductionmentioning
confidence: 99%